Implementasi Digital Marketing dalam Meningkatkan Daya Saing UMKM Keripik Permata di Kisaran Timur - Jonni Hamonangan Silaen; Benhur Pakpahan; Rehulina Bangun; Supaino Supaino; Sabarita Tarigan (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
A digital marketing mentoring program is an effective strategy for increasing the competitiveness of micro, small, and medium enterprises (MSMEs) in the digital economy era. The objective of this community service activity is to strengthen the marketing of the Permata Chips MSME through the utilization of social media, creative content production, and optimization of consistently scheduled online promotions. The methods used in implementing this program include training, direct mentoring, and content implementation to support online promotional activities. Results show a significant increase in promotional reach, more active customer interaction, improved brand perception, and increased transactions and repeat purchases. The implementation of digital marketing also provides benefits in the form of broader market expansion across regions and efficiency in the product offering process. This program is expected to become a model of capacity-based mentoring that can be replicated by other MSMEs, with implications for strengthening marketing accountability and the future sustainability of MSME businesses.